22. SKIN IRRITATION AND ANALGELIC EFFECT ON WHITE RATS WITH PERIPHERAL NEUROPATHY OF THE PREPARATION GS-TVB MASSAGE (Vietnam Journal of Community Medicine, 2025)
Objective: Research on the ability to cause skin irritation and evaluate the analgesic effect of GS-TVB massage solution in experiments.Research objects and methods: Evaluation of skin irritation ability of New Zealand White rabbits. Study of analgesic effect on sciatic nerve ligation pain model in Wistar white rats.Results: Skin irritation was assessed at (after 1 hour, 24 hours, 48 hours and 72 hours), on all 3 rabbits, in the tested skin areas, there was no sign of edema or irritation causing erythema, the average skin irritation score was 0. GS-TVB massage solution had analgesic effects through the indicators of prolonging the latency to withdraw the paw of the rats in both the cold water immersion test and the hot water immersion test; reducing the number of paw withdrawals in the paintbrush test at the measurement times after 7, 14 and 21 days of treatment (p < 0.01 compared to the model batch). This analgesic effect of GS-TVB massage solution was equivalent to that of the reference drug Voltaren emulgel.Conclusions: GS-TVB massage solution does not cause irritation on rabbit skin and has a local analgesic effect equivalent to the reference drug Voltaren gel.
Keywords: GS-TVB massage solution; skin irritation; analgesic actyvity; New Zealand White rabbits; Wistar white rats